Surveying the Role of Therapeutic Exercise in Knee and Hip Osteoarthritis: A Review study - Edris Bavardi Moghadam; Narmin Ghanizadeh Hesar; Seyed Sadradin Shojaedin (Islamic Azad University, Hamedan Branch, 2018)
Objective: The high elderly population who suffer from physical and health problems, including osteoarthritis, has a profound impact on the country's social and economic situation. Considering that therapeutic exercise is one of the essential components of OA care in the elderly, the aim of this study was to evaluate Exercise therapy in Knee and Hip Osteoarthritis. Methods: Keywords such as (Knee osteoarthritis, Hip osteoarthritis, Exercise therapy in osteoarthritis) were searched in some including databases Cinahl Eevier, PubMed, Science direct, and Google scholar. Articles selection was done based on the York University manual protocol. Results: In the initial search, 246 articles were found and in the initial review 49 duplicate articles were removed. In the second screening of the topics, the abstracts of the articles and the key words were examined and 171 articles unrelated to the content area were also excluded. Finally, based on the standard criteria and based titles on of the articles, only remained 19 articles based on which the study was conducted. The results of the studies indicated that in sports therapies, exercises aimed at improving muscle strength, aerobic capacity, flexibility, and daily weight bearing activities are commonly used useful exercises for people with osteoarthritis. Conclusion: Reviewing the findings of the previous studies, this study was able to make from a proper conclusion in relation to exercise therapy for people with osteoarthritis of the knee and hip and to partly address the training needs of this vulnerable group. The results of the study indicated that exercise therapy reduces the pain and disability of people with knee osteoarthritis, especially pelvic pain, and has a significant effect on the performance of these individuals. Also, exercises aimed at improving muscle strength, aerobic capacity, flexibility, and daily weight bearing activities are commonly used and useful exercises for people with osteoarthritis.